Money in Islamic banking system - Santoso, Bedjo; Ahmad, Khaliq; Saiti, Buerhan (Palgrave Macmillan, 2017)
The idea of revisiting currency and the gold dinar from an Islamic standpoint is an interesting topic of discussion in the context of the current monetary system. This chapter examines the historical aspects and supremacy of a gold currency and the weakness of fiat money using a maslahah-mafsadah approach. It considers some possible alternative forms of gold as money and then discusses some obstacles and barriers in the hope of finding a model of gold as money to implement in the current economic system. A deductive method is used to explore the implementation of a gold currency based on historical study and library research. The findings reveal that money is not limited to gold and silver. However, by deriving new law from original law process, the law (hukm) of gold or silver as money is permissible.